Kids through the ages - Kurnit, Paul (Henry Stewart Talks, 2010)
Insights into key issues related to communicating with youth at various ages and stages -The key concerns that rule their lives, The pressure points in understanding them, The best opportunities in effectively communicating with them, Important guide posts for marketers, parents and educators in responsibly and responsively connecting with kids